Pemanfaatan E-Book untuk Peningkatan Kemampuan Kader Posyandu dalam Integrasi Layanan Primer di Puskesmas Sungai Saren - Rafika Artisyah; Risky Kusuma Hartono (Poltekkes Kemenkes Jambi, 2025)
ABSTRACT Background: Health services provided at Posyandu (Integrated Health Posts) continue to face various challenges, particularly regarding program integration and the effectiveness of community health cadres in delivering promotive and preventive services. The Integrated Primary Health Services (ILP) program was designed to strengthen preventive approaches at the community level. However, its implementation at the Sungai Saren Community Health Center has not yet yielded optimal results. This study aims to evaluate the effectiveness of ILP implementation through the development of an e-book as an innovative learning tool for Posyandu cadres. Methods: This research applied a mixed methods approach using a sequential explanatory design. The first phase employed a qualitative phenomenological method through in-depth interviews and observations with 17 informants to explore cadres’ experiences, needs, and barriers. The second phase was a quantitative study using a quasi-experimental design (pre-test and post-test without a control group), involving 115 Posyandu cadres. The effectiveness of the intervention was assessed using the IPO framework (Input–Process–Output). Results: In the input aspect, limitations in digital literacy and access to technological devices were identified as key challenges among cadres. In the process aspect, while the e-book had reached most cadres, training and mentoring in its use remained uneven. In the output aspect, the e-book demonstrated a significant improvement in cadres’ understanding and self-confidence, particularly concerning nutrition and stunting issues. Conclusion: The ILP e-book is effective as an alternative learning medium for Posyandu cadres. However, its success depends on adaptive implementation strategies and sustained policy support.